Aeromedical Evacuation of Newborns: a Brief Review of the Literature Data and a Clinical Case of Moscow Territorial Scientific and Practical Center of Disaster Medicine - S. A. Gumenyuk; S. S. Petrikov; A. M. Schikota; V. I. Yarema (Неотложная медицинская помощь)
The issues of medical evacuation by ambulance transport are still widely discussed by specialists. The authors of the article analyzed, using a clinical case as an example, the capabilities of the aviation medical brigade in the conditions of the city of Moscow, as well as the interaction of all emergency services of the metropolis in an emergency situation.